Small bowel perforation and death caused by anaplastic thyroid carcinoma metastasis in a patient with concomitant colonic and bilateral breast carcinoma. - Jan Hrudka; Ivana Švadlenková (University of São Paulo, 2021)
Undifferentiated or anaplastic thyroid carcinoma (ATC) is rare and one of the most aggressive human malignancies. The tumor is usually voluminous and fast-growing and mostly affects older women. The most common sites of distant metastases are the lungs, brain, and bones. Herein, we describe the case of a 66-year-old woman with a history of bilateral breast carcinoma and ATC, who presented with an acute abdomen and subsequently died. At autopsy, an isolated metastasis of ATC in the small intestine leading to bowel perforation was found. Moreover, there was adenocarcinoma in the descending colon. The review of extra-abdominal malignancies metastasizing to bowel and coincidence of breast and thyroid carcinoma is included.